KOREAN POP (K-POP) DAN EKSPRESI IDENTITAS DIRI ANGGOTA FANSCLUB K-POP DI PEKANBARU - Dian Armyla Sari; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
In the early 2000s Korean pop culture was widespread in the world community and entered Indonesia, where Indonesian people were focused on South Korea who was holding a world cup, besides that Indonesian private television stations broadcast many Korean dramas that drew the attention of Indonesian people. Finally, Korean pop culture can form K-pop fan clubs in Indonesia to be widespread in cities like Pekanbaru. On February 10, 2012 the Pekanbaru K-popers community was formed. This study aims to determine the activities of Pekanbaru K-pop fansclub and the expression of the identity of the fansclub members. The method used in this study is qualitative in which the researcher gets 9 selected subjects using purposive sampling to meet the criteria determined by the researcher. The results of this study stated that they carry out activities that contain symbol consumption both on social media and in real life, they also like to collect K-pop items, they show that they are K-popers during fansclub activities or K-popers communities, using attributes and every day they only use ordinary accessories such as pins and bag hangers. They realize the impact and benefits of being K-popers, from positive things to being diligent in saving, being independent and working hard to achieve something and from negative things they become wasteful in buying K-pop goods, spending money on K-pop activities such as ganthering, watching concerts and other K-pop activities as well as their activities with their own world. Keyword: Korean pop, Expression, Identity